RENCANA STRATEGIS ORGANISASI TEKNOLOGI INFORMASI DI PT PERKEBUNAN NUSANTARA X DENGAN METODE CASCADING BALANCED SCORECARD - Rizal, M. Syaiful; E.R., Mahendrawathi; Noor Ali, Achmad Holil (UNUSA Press, 2018)
PT Perkebunan Nusantara X (PTPN X) is a state-owned company engaged in the sugar industry and tobacco as well as a number of subsidiaries. PTPN X uses Information Technology (IT) to improve productivity and competitive advantage. The Management of PTPN X generated IT Organization to deliver good IT solution. But with the limited budget and a huge investment, the role of IT is not contributing the maximum to the progress of the company even IT solution have paradox impact. This is because the IT strategic initiatives do not aligned with its business strategy, so that IT organizations need strategic planning. In This study, strategic planning for IT organization generated by using the Balanced Scorecard Cascading. Wherein the process is divided into several stages, namely the determination of the vision and mission of IT organizations, determine business strategy that will be supported by IT, identification of IT users, identification of output and the main job description of the IT organization, aligning strategy IT organizations indicated to the strategic map, defining Key Performance Indicators (KPIs), and IT strategic initiatives of each strategies. The analysis in this study is using SWOT analysis, Critical Success Factor, and Value Chain. Balanced Scorecard is used in this study were IT-Balanced Scorecard with the perspectives of Corporate Contribution, Customer Orientation, Operational Excellence, and Future Orientation. The results obtained from this research are 10 Strategy that is maximizing IT contribution to business, meet the IT customers’ needs, good IT planning, implementing good application, effective and efficient IT operations, improving IT good services, upgrades IT and Technology support, IT good governance implementation, IT alignment with business strategy, and motivated and competent IT personnel. There are 21 KPI to measure the strategy and 30 strategic initiatives or programs to meet the KPI. The KPI and the 30 initiatives are arranged based on the existing condition of IT organization reflected in the SWOT and what targets are indeed to be achieved by implementing the strategy.